Prognostic value of body adipose tissue parameters in cancer patients treated with immune checkpoint inhibitors - Li, Yan; Yu, Yean; Lv, Kun; Ge, Rongjuan; Xie, Xie (Frontiers in Immunology, 2025)
ObjectiveThis study aims to explore the relationship between body adipose tissue characteristics and clinical outcomes in cancer patients receiving immune checkpoint inhibitor (ICI) therapy.MethodsWe conducted an extensive literature search across three major online databases—Embase, PubMed, and the Cochrane Library—to identify studies examining the link between body adipose tissue and treatment outcomes in cancer patients undergoing ICI therapy, from the inception of each database until February 20, 2024. The quality of the included studies was evaluated using the Newcastle-Ottawa Scale. The primary outcomes analyzed were hazard ratios (HRs) for overall survival (OS) and progression-free survival (PFS), as well as odds ratios (ORs) for disease control rate (DCR). Pooled estimates and 95% confidence intervals (CIs) were calculated.ResultsA total of 23 studies were included, encompassing 2741 cancer patients. The analysis revealed that patients with higher levels of visceral adipose tissue (VAT) exhibited significantly improved OS (HR: 0.72, 95% CI: 0.59–0.89, p < 0.001) and PFS (HR: 0.80, 95% CI: 0.67–0.96, p = 0.015), along with a higher DCR (OR: 1.81, 95% CI: 1.26–2.60, p = 0.001), compared to those with lower VAT levels. Additionally, increased subcutaneous adipose tissue (SAT) levels were associated with significantly better OS (HR: 0.69, 95% CI: 0.58–0.82, p < 0.001) and PFS (HR: 0.82, 95% CI: 0.68–1.00, p = 0.049), and a higher DCR (OR: 1.99, 95% CI: 1.15–3.44, p = 0.014). Elevated total adipose tissue (TAT) levels were also linked to longer OS (HR: 0.73, 95% CI: 0.55–0.97, p = 0.028). However, a higher visceral-to-subcutaneous adipose tissue ratio (VSR) was associated with a shorter OS (HR: 1.43, 95% CI: 1.09–1.87, p = 0.010). No significant relationship was found between TAT (HR: 0.81, 95% CI: 0.54–1.23, p = 0.332) and VSR (HR: 1.20, 95% CI: 0.95–1.51, p = 0.131) with PFS in ICI-treated patients.ConclusionThis study highlights the prognostic relevance of VAT and SAT in predicting treatment response and survival outcomes in cancer patients receiving ICIs. These findings suggest that assessments of VAT and SAT should be incorporated into prognostic evaluations for this patient population.